Correlation analysis of gamma-glutamyl transferase to lymphocyte ratio and patients with acute aortic syndrome in China: a propensity score-matched analysis - Li, Minhong; Xu, Weimin; Chen, Hongchun; Lai, Yidong; Chen, Yequn; Shu, Zhouwu; Tan, Xuerui (Frontiers in Cardiovascular Medicine, 2024)
Background and Objectives: Acute aortic syndrome (AAS) is a life-threatening condition in which there is a fracture in the integrity of the aortic wall. gamma-glutamyl transferase to lymphocyte ratio (GLR) is recognized as a risk factor for liver cirrhosis, fibrosis, and hepatocellular carcinoma. However, there are no clinical reports of GLR and AAS. We attempted to determine whether GLR level is associated with AAS in patients from the Chaoshan region of southern China.Methods: A total of 2384 patients were recruited in this study and were divided into AAS and no-AAS groups according to the results of CT angiography of the thoracoabdominal aorta. Univariate and multivariate logistic regression was performed to identify risk factors for the occurrence of AAS. ROC was applied to assess the value of D-Dimer, GLR alone, or in combination for the diagnosis of AAS. And a 1:1 propensity score-matched analysis was performed.Results: Multivariate logistics regression analysis indicated that male, age, hypertension, diabetes, creatinine, D-dimer, and GLR were independent risk factors of AAS patients in the before propensity scorematching cohort. After propensity score-matching, It showed that D-dimer, GLR［OR 3.558(1.891，6.697)； p＜0.001］were independent risk factors of AAS patients. Before propensity score-matching, the area under the curve (AUC) was 0.822 of GLR and 0.767 of D-dimer. When both clinical backgrounds were adjusted, the AUC was 0.773 of GLR and 0.631 of D-dimer. GLR showed high specificity (80.5% and 77.1%), and D-dimer showed high sensitivity (84.7% and 73.6%) in the before and after propensity score-matching cohort.GLR and D-dimer were independent risk factors of acute aortic syndrome. D-dimer in combination with GLR is more valuable than a single indicator for diagnosing acute aortic syndrome.